KEBIJAKAN HUTANG: STRUKTUR ASET, PROFITABILITAS DAN PELUANG PERTUMBUHAN - ANGGISTA PUSPITA DEWI; ANI WILUJENG SURYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to determine the influence of asset structure, profitability and growth opportunity on debt policy. Data were collected from 16 Indonesia building construction companies annual reports from 2014 to 2017. The asset structure was measured using fixed assets ratio (FAR), profitability using return on assets (ROA), growth opportunity using price earnings ratio (PER) and debt policy using a debt to equity ratio (DER). The hypothesis was examined using panel data regression analysis. The results showed that the asset structure has a significant positive effect on debt policy, while profitability has a significant negative effect. However, growth opportunity shows no effect on debt policy. The results of this study can be input for companies need to consider increasing profitability in meeting company funds, so that external funding needs are not high. In addition, company managers need to maintain the level of debt to maintain the reputation and trust of external parties to the company and prevent financial distress.